2000
DOI: 10.1212/wnl.55.10.1584
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia with vitamin E deficiency: Biochemical effects of malcompliance with vitamin E therapy

Abstract: To prevent neuronal damage, patients with ataxia with isolated vitamin E deficiency need lifelong supplementation with high doses of vitamin E. Short interruptions of therapy, such as occur in malcompliance, do not lead to clinical symptoms. However, the authors show that even short withdrawals may cause a prolonged decrease of the total radical trapping capacity of plasma; its major contributors, such as urate and sulfhydryl groups, fail to compensate for the missing vitamin E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
0
16
0
2
Order By: Relevance
“…Cardiac involvement was also rare, occurring only in Moroccan and Tunisian patients. Several other symptoms, such as dystonia (Yokota et al, 1987;Cavalier et al, 1998;Schuelke et al, 2000;Angelini et al, 2002), myoclonus (Yokota et al, 1987;Angelini et al, 2002), tongue fasciculations (Martinello et al, 1998;Roubertie et al, 2003) and deafness (Shimohata et al, 1998;Usuki et al, 2000), are considered to be rare findings in patients with AVED and were not observed in our patients. Wheelchair-bound age reported for some of our patients was variable, as reported by Cavalier et al (1998), andMariotti et al (2004) despite vitamin E treatment.…”
Section: Clinical Featuresmentioning
confidence: 64%
“…Cardiac involvement was also rare, occurring only in Moroccan and Tunisian patients. Several other symptoms, such as dystonia (Yokota et al, 1987;Cavalier et al, 1998;Schuelke et al, 2000;Angelini et al, 2002), myoclonus (Yokota et al, 1987;Angelini et al, 2002), tongue fasciculations (Martinello et al, 1998;Roubertie et al, 2003) and deafness (Shimohata et al, 1998;Usuki et al, 2000), are considered to be rare findings in patients with AVED and were not observed in our patients. Wheelchair-bound age reported for some of our patients was variable, as reported by Cavalier et al (1998), andMariotti et al (2004) despite vitamin E treatment.…”
Section: Clinical Featuresmentioning
confidence: 64%
“…We found that E− larvae sustain marked locomotor deficits in response to light/dark stimuli (Figure 2). An established symptom of overt VitE deficiency in humans and rodent is spinocerebellar ataxia [28,29], therefore outcomes of our locomotor assay alone were insufficient to indicate specifically cognitive impairments in the E− larvae because lasting motor-related neuropathologies could contribute to the reduced locomotor response observed in the E-group. To deduce specifically whether this outcome was due to cognitive, motor, or perceptual (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Malabsorption of vitamin E, including in abetalipoproteinaemia, can result in a similar phenotype. Patients may need replacement doses of up to 1500 mg/day 15…”
Section: Introductionmentioning
confidence: 99%